Analisis Kesulitan Siswa SMA Kelas XI Dalam Mempelajari Ukuran Tendensi Sentral - Aulia Ar Rakhman Awaludin (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2017)
This study aims to determine the difficulties of learning what are the natural students of class XI SMA Batik 1 Surakarta on the material statistics the size of the central tendency of group data, what causes the difficulty of learning students class XI SMA Batik 1 Surakarta on the material statistics the size of the central tendency of group data and how the alternative Solving the results of the analysis of learning difficulties on the statistical matter of the size of the central tendency of group data. The method used is literature study. Alternative results for students who have difficulty in understanding the concept is to apply learning contextual approach is learning that aims to motivate students to understand the meaning of the material in the learning by associating with the context of everyday life such as knowing the average of a value of repetition, know mode (value Which many students get) from a repetition so that learning will be memoras and remembered by students and for students who have difficulty application of formulas and solutions is the alternative given is to multiply the exercise questions and need for the elaboration of what is known and can be from where. When students are accustomed to such things then students will be easy in applying the formula and solve the problem correctly.